Analysis Of Challenges and Strategies In Implementing Pancasila Student Profile Values Through The Introduction Of Local Wisdom in School - Majid, Novita; Wingkolatin, Wingkolatin; Asnar, Asnar; Aini, Nur (Faculty of Teacher Training and Education, Mulawarman University, 2024)
The Pancasila student profile has urgency in fixing problems related to the nation's noble values ​​and morals, as well as improving the quality of education in Indonesia. The six Pancasila student profile indicators cannot be separated from the 2020-2035 education road map. Efforts to integrate local wisdom in Civics learning provide a bridge for the younger generation. The method in this research is qualitative with descriptive analysis and data collection techniques in the form of interviews, questionnaires, literature studies and documentation. This research aims to analyze the obstacles and efforts to apply the values ​​of the Pancasila student profile in PPKn learning from the implementation of local wisdom activities for 7th generation teaching campus students. The results of the research explain that there are obstacles in implementing the Pancasila profile for students at SMPN 8 Tenggarong, namely internal and external factors. Internal factors: different student characteristics, lack of student literacy skills, lack of teacher understanding of the project to strengthen the Pancasila profile, limited use of media and teacher limitations in designing lesson plans; external factors, less than optimal government implementation, lack of support from some parties, and limited time for teaching and learning activities. efforts to implement students' Pancasila profile values ​​through the introduction of local wisdom in schools, namely: integrating local wisdom into intracurricular, co-curricular and extracurricular learning materials; Teachers are given training on how to integrate local wisdom in the learning process, because teachers have a central role in the knowledge transfer process; and Adequate infrastructure required.